ANALISIS TINGKAT KESEHATAN BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH DENGAN METODE CAMELS DAN RGEC - Fortrania, Lotus Mega; Oktaviana, Ulfi Kartika (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Banking should always be assessed health to stay fit in serving the customers,the Bank that classified unhealthy can inflict the bank institution itself and ofthe others, namely the customers of the bank. To assess a health bank can beviewed from various aspects of assessment, this research aimed to determinewhether the bank is in a very healthy, healthy, healthy enough, less healthy orunhealthy. There were several methods that can be used to assess or analyzethe health of the banking, namely CAMEL, CAMELS and RGEC. This researchwas a quantitative research, with descriptive approach. The data used wassecondary data on 34 banking companies consisted of 11 companies of Syariapublic banks and 23 companies of Syaria business units. Analysis conductedin this study was to use the calculation of financial ratios that have been set bythe financial services authority. The results showed that the health level ofSyaria public Bank and Syaria Business Unit with using CAMELS method andRGEC showed health predicate of the bank in accordance with the standardsset by Bank Indonesia, for the period 2011 can be concluded that the Syariapublic Banks and Sharia Business Unit of composite rankings â€HEALTâ€, theperiod of 2012 with the conclusion of composite rating â€HEALTâ€, and for theperiod of 2013 with the conclusion of composite rating â€HEALTâ€. RGECmethod can be said to be better than in the two previous methods, namelyCAMELS and CAMEL, through RGEC, BI (Bank Indonesia) wanted banks tobe able to identify problems early, performed the appropriate and faster follow-up improvements, and implemented Good Corporate Governance (GCG) andbetter risk management so banks will be more resilient in the face of crisis